O-GlcNAcylated FTO promotes m6A modification of SOX4 to enhance MDS/AML cell proliferation - Junjie Gou; Jingjing Bi; Kexin Wang; Lei Lei; Yanli Feng; Zengqi Tan; Jiaojiao Gao; Yanan Song; Enci Kang; Feng Guan; Xiang Li (Cell Communication and Signaling)
Abstract Fat mass and obesity-associated protein (FTO) was the first m6A demethylase identified, which is responsible for eliminating m6A modifications in target RNAs. While it is well-established that numerous cytosolic and nuclear proteins undergo O-GlcNAcylation, the possibility of FTO being O-GlcNAcylated and its functional implications remain unclear. This study found that a negative correlation between FTO expression and O-GlcNAcylation in patients with myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). The decreased O-GlcNAcylation on FTO can result in diminished m6A modification of SRY-related high mobility group box 4 (SOX4). This led to the promotion of cell apoptosis and inhibition of cell proliferation in MDS/AML. The O-GlcNAcylation of FTO stabilized SOX4 transcripts in an m6A-dependent manner, resulting in increased AKT and MAPK phosphorylation and decreased cell apoptosis. Inhibiting FTO O-GlcNAcylation significantly slowed AML progression in vitro, a finding supported by clinical data in MDS/AML patients. In conclusion, our study highlights the crucial role of FTO O-GlcNAcylation in RNA m6A methylation and the progression of MDS/AML, thereby providing a potential therapeutic avenue for these formidable diseases.